Species-Specific Marker Discovery in Tilapia - Syaifudin, Mochamad (Sci Rep, 2019)
Tilapias (family Cichlidae) are of importance in aquaculture and fisheries. Hybridisation and introgression are common within tilapia genera but are difficult to analyse due to limited numbers of species-specific genetic markers. We tested the potential of double digested restriction-site associated DNA (ddRAD) sequencing for discovering single nucleotide polymorphism (SNP) markers to distinguish between 10 tilapia species. Analysis of ddRAD data revealed 1,371 shared SNPs in the de novo-based analysis and 1,204 SNPs in the reference-based analysis. Phylogenetic trees based on these two analyses were very similar. A total of 57 species-specific SNP markers were found among the samples analysed of the 10 tilapia species. Another set of 62 species-specific SNP markers was identified from a subset of four species which have often been involved in hybridisation in aquaculture: 13 for Oreochromis niloticus, 23 for O. aureus, 12 for O. mossambicus and 14 for O. u. hornorum. A panel of 24 SNPs was selected to distinguish among these four species and validated using 91 individuals. Larger numbers of SNP markers were found that could distinguish between the pairs of species within this subset. This technique offers potential for the investigation of hybridisation and introgression among tilapia species in aquaculture and in wild populations.